Peranan Adaptabilitas, Orientasi Kewirausahaan dan Inovasi dalam Meningkatkan Kinerja Usaha Mikro (Studi pada Industri Kerajinan Rotan di Kalimantan Selatan) - Hidayatullah Hidayatullah (At-Taradhi Jurnal Studi Ekonomi, 2019)
Adaptability, entrepreneurial orientation, and innovation are important intangibles resources that micro business can use to gain a competitive advantage. Drawing upon the Resource-Based view (RBV) of the firm, this study in general examines empirically and analysis the role of adaptability, entrepreneurial orientation and Innovation in improving the performance of micro business. The objective of this research in particular are: (1) examines empirically and analysis the role of adaptability in improving the business performance directly and indirectly through entrepreneurial orientation and innovation. (2) examines empirically and analysis the role of entrepreneurial orientation in improving the business performance directly and indirectly through innovation.Population in this research is all micro business of the Rattan-craft industry in the districts of Hulu Sungai Utara and Tapin in South Kalimantan Province. Those are 244 units. Sampling method is Proportional Area Random Sampling. Total sample in this research are 152 micro businesses. Data was analyzed by SEM (Structural Equation Model) through AMOS program.The results showed that (1) adaptability plays a positive role in improving the entrepreneurial orientation and innovation, but not for business performance; adaptability has an indirect effect on business performance through innovation (2) entrepreneurial orientation plays a positive role in improving on innovation directly and business performance indirectly through innovation. This research has given some research limitation, implication and also give an agenda for the further research.